2007
DOI: 10.1086/518475
|View full text |Cite
|
Sign up to set email alerts
|

The Galaxy Luminosity Functions down toM~ -10 in the Hydra I Cluster

Abstract: We study the galaxy population of the Hydra I cluster in the central region and a region about 0.6 Mpc away from its center in the B and R C bands down to M $ À10 using Subaru Suprime-Cam photometry. We find that the luminosity function of the entire population has a slightly steeper slope ( $ À1:6) in the range of À20 < M < À10 than those reported for other clusters in slightly brighter ranges. The slope appears to be steeper in poorer clusters. The number of faint galaxies (M > À14) increases in the cluster … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 55 publications
0
16
1
Order By: Relevance
“…Sabatini et al 2003;Milne et al 2007, and references therein). The LF of the Hydra I cluster has previously been determined by Yamanoi et al (2007) who find α ∼ −1.6 in the magnitude range −20 < M B,R < −10. This is a steeper slope than reported by Yagi et al (2002) who give α = −1.31 for the faint end slope of the composite LF of 10 nearby clusters (including Hydra I) at −23 < M R < −16.…”
Section: The Galaxy Luminosity Functionmentioning
confidence: 83%
See 2 more Smart Citations
“…Sabatini et al 2003;Milne et al 2007, and references therein). The LF of the Hydra I cluster has previously been determined by Yamanoi et al (2007) who find α ∼ −1.6 in the magnitude range −20 < M B,R < −10. This is a steeper slope than reported by Yagi et al (2002) who give α = −1.31 for the faint end slope of the composite LF of 10 nearby clusters (including Hydra I) at −23 < M R < −16.…”
Section: The Galaxy Luminosity Functionmentioning
confidence: 83%
“…Recently, Yamanoi et al (2007) found α ∼ −1.6 for the cluster LF. Our observed fields overlap with their central observed region and we reach a similar limiting magnitude.…”
Section: The Hydra I Lfmentioning
confidence: 98%
See 1 more Smart Citation
“…As most SNe Ia occur in massive galaxies, it is difficult to assess whether they might also have an enhanced rate in dwarf galaxies because of the large statistical uncertainty on the rate due to the relatively low number of SNe Ia in lowmass hosts (e.g., Quimby et al 2012). SN surveys of rich galaxy clusters are an efficient way to search many low-mass galaxies at once, owing to both a higher sky density of galaxies and the (putative) upturn in the faint-end slope of the cluster luminosity function (e.g., Milne et al 2007;Yamanoi et al 2007). In this work we find that one IC SN Ia may be hosted by a dwarf cluster galaxy, and we discuss the implications of this for SN Ia rates in faint hosts.…”
Section: Sn Ia Rates In Faint Hostsmentioning
confidence: 99%
“…Because few deep spectroscopic surveys of clusters extend into the dwarf galaxy regime (M r −18; for exceptions, see Mobasher et al 2003;Christlein & Zabludoff 2003;Mahdavi et al 2005, and references therein), cluster membership is usually determined via statistical subtraction of background galaxies (e.g., Popesso et al 2006;Jenkins et al 2007;Milne et al 2007;Adami et al 2007;Yamanoi et al 2007; Barkhouse et al 2007, and references therein). Because galaxy number counts increase much more steeply than cluster member counts (even for very steep faint-end slopes), small systematic uncertainties in background subtraction can produce large uncertainties in the abundance of faint cluster galaxies.…”
Section: Introductionmentioning
confidence: 99%